A dialogicidade no ensino de Filosofia: a ressignificação do diálogo pedagógico pela lógica - PEREIRA, Milla Tamires Amorim (2019)
A significant part of the literature on philosophy teaching points out that philosophy must go through the process of philosophizing, striving for dialogue. However, these studies do not seem to place sufficient emphasis on the research tools that are indispensable in the construction of philosophical knowledge, and for this reason, the proposed dialogical methods have often been shown to be shallow and wordy in everyday pedagogical practice. Thus, a resignification of this dialogue that is proposed as a method of teaching philosophy is necessary, inserting in it, as a prior task, the domain of logical tools of argumentation. The study is qualitative and will be developed in a public school of the state school system, with the main objective to verify if there is any noticeable impact after the previous study of informal logic in the occurrence of an effective dialogic class characterized by the Socratic dialectic as method of problematizing, investigating and reframing concepts, thus representing the very act of philosophizing. The strategy used consists of didactic sequences in philosophy classes focused on the study of argumentation and the simultaneous monitoring of didactic performance in philosophy classes. From the observed results, we intend to identify advantages and deficiencies in the approach employed, as well as offer recommendations involving the adoption of similar strategies aiming at the same objectives.